Exploring the dynamics of food-related policymaking processes and evidence use in Fiji using systems thinking - Gade Waqa; Marj Moodie; Wendy Snowdon; Catherine Latu; Jeremaia Coriakula; Steven Allender; Colin Bell (BMC, 2017)
Abstract Background Obesity and non-communicable diseases are significant public health issues globally and particularly in the Pacific. Poor diet is a major contributor to this issue and policy change is a powerful lever to improve food security and diet quality. This study aims to apply systems thinking to identify the causes and consequences of poor evidence use in food-related policymaking in selected government ministries in Fiji and to illicit strategies to strengthen the use of evidence in policymaking. Methods The Ministry of Health and Medical Services and the Ministry of Agriculture in Fiji were invited through their respective Permanent Secretaries to participate in the study. Three 180-minute group model building (GMB) workshops were conducted separately in each ministry over three consecutive days with selected policymakers who were instrumental in developing food-related policies designed to prevent non-communicable diseases. The GMB workshops mapped the process of food-related policymaking and the contribution of scientific and local evidence to the process, and identified actions to enhance the use of evidence in policymaking. Results An average of 10 policymakers participated from each ministry. The causal loop diagrams produced by each ministry illustrated the causes and consequences of insufficient evidence use in developing food policies or precursors of the specific actions. These included (1) consultation, (2) engagement with stakeholders, (3) access and use of evidence, and (4) delays in policy processes. Participants agreed to potential leverage points on the themes above, addressing pertinent policymaker challenges in precursor control, including political influence, understanding of trade policies, competing government priorities and level of awareness on the problem. Specific actions for strengthening evidence use included training in policy development and research skills, and strengthening of coordination between ministries. Conclusions The GMB workshops improved participants' understanding of how different parts of the policy system interact. The causal loop diagrams and subsequent action plans enabled the identification of systems-level interventions in both ministries to improve evidence-informed policy development. A guide for integrating multi-sectoral consultation and stakeholder engagement in developing cross-cutting policies is currently being developed.